The Protection of Legal Order by Administrative Courts - Grzybowski, Tomasz; Sarnowiec-Cisłak, Marta (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The position of the administrative judiciary, as it has functioned since 2004, situates this institution not only as a guarantor of the legality of public authority action in a given case, but also of the coherence and functionality of the administrative law system as such. The protection of the legal order by administrative courts is naturally related to the issue of the stability of the judicial practice and the responsibility of the judge for the content of the ruling, and further to the effectiveness of the judicial-administrative application of the law. Thus, this issue is situated on the edge of different methodological planes, covering such threads of analysis as: the place and role of administrative courts in the modern legal order (constitutional-legal method), the procedural model of judicial application of law and its effectiveness (administrative-legal method), or theoretical and even ethical-legal aspects of judicial application of law. In the light of the decisional model of judicial application of law, the issue of care for legal order is revealed with particular force in the layer of validation and interpretation findings, which gives significant importance to the reasons for the justification, especially if one takes into account that the execution of the decision in principle remains outside the competence of the administrative court. Against this background authors pay attention on the relatively restrained use of reformatory powers and disciplinary measures by administrative courts, as a kind of last resort legal remedy. This allows to maintain thesis that administrative courts generally protect the legal order with the force of arguments rather than with the argument of force. On the other hand, they treat measures to ensure the certainty and effectiveness of decisions of judicial application of law as measures to protect the legal order.